Distribution and ecology of planktic foraminifera in the North Pacific: Implications for paleo-reconstructions. (1st July 2018) - Taylor, Ben J.; Rae, James W.B.; Gray, William R.; Darling, Kate F.; Burke, Andrea; Gersonde, Rainer; Abelmann, Andrea; Maier, Edith; Esper, Oliver; Ziveri, Patrizia
Abstract: Planktic foraminifera census data have been used to reconstruct past temperatures through transfer functions, as well as changes in ocean ecosystems, chemistry and circulation. Here we present new multinet, plankton net and core-top census data from 20 sites in the Subpolar North Pacific. We combine these with previous data to provide an up to date compilation of North Pacific planktic foraminifera assemblage data. Our compilation is used to define 6 faunal zones: the subpolar zone; transitional zone; upwelling zone; subtropical zone; east equatorial zone; west equatorial zone; based on the distribution of 10 major species of planktic foraminifera. Two species of planktic foraminifera Neogloboquadrina pachyderma and Globigerina bulloides provide the basis for many subpolar paleo-reconstructions. Through the analysis of new multinet and CTD data we find that G. bulloides and N. pachyderma are predominantly found within 0–50 m of the water column and coincide with high food availability. N. pachyderma also shows a strong temperature control and can thrive in food poor waters where temperatures are low. Both species bloom seasonally, particularly during the spring bloom of March to June, with G. bulloides exhibiting greater seasonal variation. We suggest that percentage abundance of N. pachyderma in paleo-assemblages can be used to assess relative changes in past temperature, with G. bulloides abundance more likely to reflect changes in food availability. By comparing our core-top and multinet data, we also find a dissolution bias of G. bulloides over N. pachyderma in the North Pacific, which may enrich assemblages in the latter species. Highlights: G. bulloides and N. pachyderma are mainly found in the top 50 m. Food availability is the main driver of abundance in G. bulloides. Temperature is the dominant control on N. pachyderma abundance. Dissolution may bias assemblage records towards resistant planktic foraminifera.